Absolute returns : the risk and opportunities of hedge fund investing - Ineichen, Alexander M. (New York : John Wiley & Sons, Inc., 2003)
The hedge fund business is about achieving excellent risk-adjusted returns, not about beating the market. In other words, the hedge fund business is about absolute returns. this book will introduce you to the new investment paradigm of absolute returns, outline the risk and opportunities of absolute return strategies, dispel the myths and misconceptions that have surrounded hedge funds and provide a detailed look at the advantages and disadvantages of hedge fund investing.
Includes bibliographical references (p. 484-498) and index.
nmn 23/09/16; 0pc 30/09/16
Loans
Keywords: Hedge funds